Behaviour of externally prestressed beams - Chan, Kim Liang (2004)
Externally prestressed beams are defined as structural concrete beams with external prestressing tendons placed outside the concrete section. The behaviour of externally prestressed beams was studied by evaluating the flexural response of the beam based on modified bond reduction coefficients to account for second order effects and using a structural software to model the overall behaviour of the beam with incremental loading. Theoretical calculations based on modified bond reduction coefficients were found to be acceptable within the test results. The predicted results from computer modeling showed that the structural behaviour of externally prestressed beam can be satisfactorily predicted from initial zero load to the ultimate loading stage.